Design and Development of an Android-Based Point of Sale Application: A Case Study of Warung Dapur Barokah, Pangkalpinang - Hanif, Ahmad; Suhendar, Agus; Sejati, Rr. Hajar Puji (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Warung Dapur Barokah is a food stall in Pangkalpinang City and was founded in 2022. This application was designed to overcome obstacles that generally arise in manual transaction processes, which are often slow, inefficient, and difficult to manage accurately sales data. This application was developed using Android Studio and adopted the Kotlin programming language. Apart from that, the database section uses Firebase. I am using Firebase because Firebase has a real-time databaseRealtime that can update data in the database in realtime. This will make the transaction data storage process synchronized, fast, and optimal. The hope is that the results of implementing this application will include increased efficiency and speed in the transaction process and potentially improve the profitability of Warung Dapur Barokah's operations. This innovation is hoped to positively contribute to advancing the operational performance of this food stall in the current digital era, as well as creating effective solutions to increase the competitiveness and sustainability of local businesses in the culinary sector.